Complex Population Dynamics : A Theoretical/Empirical Synthesis (MPB-35) - Turchin, Peter, 1957- (Book collections on Project MUSE., 2003)
Why do organisms become extremely abundant one year and then seem to disappear a few years later? Why do population outbreaks in particular species happen more or less regularly in certain locations, but only irregularly (or never at all) in other locations? Complex population dynamics have fascinated biologists for decades. By bringing together mathematical models, statistical analyses, and field experiments, this book offers a comprehensive new synthesis of the theory of population oscillations.